Conflict minerals and supply chain due diligence: an exploratory study of multi-tier supply chains - Hofmann, Hannes; Schleper, Martin C.; Blome, Constantin (Springer, 2018)
As recently stakeholders complain about the use of conflict minerals in consumer products that are often invisible to them in final products, firms across industries implement conflict mineral management practices. Conflict minerals are those, whose systemic exploitation and trade contribute to human right violations in the country of extraction and surrounding areas. Particularly, supply chain managers in the Western world are challenged taking reasonable steps to identify and prevent risks associated with these resources due to the globally dispersed nature of supply chains and the opacity of the origin of commodities. Supply chain due diligence (SCDD) represents a holistic concept to proactively manage supply chains reducing the likelihood of the use of conflict minerals effectively. Based on an exploratory study with 27 semi-structured interviews within five European industries, we provide insights into patterns of implementation, key motivational factors, barriers and enablers, and impacts of SCDD in mineral supply chains. Our results contribute to both theory and practice as we provide first insights to SCDD practices and make recommendations for an industry-wide implementation of SCDD. Altogether, this study provides the basis for future theory testing research in the context of SCDD and conflict mineral management.